2014
DOI: 10.1021/ja510831n
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Spectroscopic, and Theoretical Comparison of Traditional vs Recently Discovered Ln2+ Ions in the [K(2.2.2-cryptand)][(C5H4SiMe3)3Ln] Complexes: The Variable Nature of Dy2+ and Nd2+

Abstract: The Ln(3+) and Ln(2+) complexes, Cp'3Ln, 1, (Cp' = C5H4SiMe3) and [K(2.2.2-cryptand)][Cp'3Ln], 2, respectively, have been synthesized for the six lanthanides traditionally known in +2 oxidation states, i.e., Ln = Eu, Yb, Sm, Tm, Dy, and Nd, to allow direct structural and spectroscopic comparison with the recently discovered Ln(2+) ions of Ln = Pr, Gd, Tb, Ho, Y, Er, and Lu in 2. 2-La and 2-Ce were also prepared to allow the first comparison of all the lanthanides in the same coordination environment in both +2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

38
295
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(336 citation statements)
references
References 89 publications
38
295
2
1
Order By: Relevance
“…106 However, chemists never stopped pushing synthetic limits and, recently, low valent lanthanide chemistry has emerged as a fast developing field. [107][108][109] Recent advancements feature the synthesis and characterization of divalent lanthanide complexes for the complete lanthanide series, [110][111][112][113][114][115][116] reduced dinitrogen complexes, [117][118][119][120][121] reduced arene complexes, 26-29, 57, 122-126 and bimetallic reductive cleavage of aromatic C-H bonds. 40,44 Our group focused on the reduction chemistry of rare-earth metal complexes with non-innocent  ligands, followed by a small molecule activation study.…”
Section: Reduction Chemistry With  Ligands and Small Molecule Actmentioning
confidence: 99%
“…106 However, chemists never stopped pushing synthetic limits and, recently, low valent lanthanide chemistry has emerged as a fast developing field. [107][108][109] Recent advancements feature the synthesis and characterization of divalent lanthanide complexes for the complete lanthanide series, [110][111][112][113][114][115][116] reduced dinitrogen complexes, [117][118][119][120][121] reduced arene complexes, 26-29, 57, 122-126 and bimetallic reductive cleavage of aromatic C-H bonds. 40,44 Our group focused on the reduction chemistry of rare-earth metal complexes with non-innocent  ligands, followed by a small molecule activation study.…”
Section: Reduction Chemistry With  Ligands and Small Molecule Actmentioning
confidence: 99%
“…Moreover, recent work has shown that ligand fields can be used to tune lanthanide redox chemistry 65,[104][105][106][107][108][109] and ground state electronic configurations. [110][111][112][113][114][115] Clearly, efforts to advance understanding of the roles that covalency and electronic structure play in governing chemical and physical properties would benefit from broader integration of synthetic, spectroscopic, and theoretical research efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Yttrium was the initial metal of choice due to its favorable NMR characteristics associated with a 100% naturally abundant I = 1/2 89 Y nucleus. To contrast the chemistry of this smaller rare earth ion with that of larger metal ions, the analogous reactions with the largest lanthanides, lanthanum and cerium, 19 were examined. The dysprosium analogue 19 was also studied as a typical openshell lanthanide and a member of the set of traditional six Ln 2+ ions described above.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To contrast the chemistry of this smaller rare earth ion with that of larger metal ions, the analogous reactions with the largest lanthanides, lanthanum and cerium, 19 were examined. The dysprosium analogue 19 was also studied as a typical openshell lanthanide and a member of the set of traditional six Ln 2+ ions described above. Not only was reduction of aromatic substrates observed, but these reactions also led to the isolation of the tetrakis(trimethylsilylcyclopentadienyl) complexes, (Cp′ 4 Ln) − .…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation